The value of human life in the culture of postmodernity in the light of John Paul II’s Encyclical “Evangelium vitae” - Ozorowski, ks. Mieczysław (Studia Teologiczne Białystok Drohiczyn Łomża, 2025)
Article on the value of human life in the context of contemporary European culture, based on the encyclical "Evangelium vitae" of John Paul II. believes that human life is sacred and must be protected from conception to death, while pointing out the contemporary threat of the "culture of death" that undermines these basic values. The author on the principle of promoting a "culture of life" that respects the dignity and inviolability of human life, as a response to the growing moral relativism and dehumanization in society.